In Defence of Orthodoxy. Anti-Heretic and Anti-Muslim Voices in Palaea – History, Typology, Textology - Skowronek, Małgorzata (Phantom of Muhammad, Shade of Samuel Byzantine Empire in Relation to Members of Other Cultures and Religions (7th–15th c.): No. XXXIX, 2020)
The article is dedicated to the overview of polemic texts (anti-heretic texts, anti-Muslim texts), that were included over a couple centuries in the structure of a literary artefact, known as Palaea.